Sosialisasi Undang-Undang Nomor 11 Tahun 2008 Tentang ITE Oleh Pemerintah Jawa Barat - Noneng Sumiaty; Syaidah (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2014)
This Research be held at ten cities and regencies on West Java Province. This study aims to determine the attitude of Local Government in the implementation, barriers and solutions about the ITE Law socialization.This research method is descriptive qualitative approach. Technique Data collected through observation, depth interviews with key informants, namely the Regional Officer or a representative who knows about the socialization of the ITE Law.The results showed that the attitude of the West Java Regional Government on the implementation of socialization, when viewed from the aspect of understanding, aspects of interest and awareness of the importance of socialization, expressed understanding, interest and was well aware that the ITE Law socialization is very important. Only two areas that have been carried out socialization. Barriers in socialization, lack of stakeholder-led policy makers and policy-making, and the absence of a special fund allocation. The solution is to send a representative from the Region to participate in the Central or Provincial socialization and prepare materials and a special fund to socialize UU ITE. Keywords: Socialization, UU ITE, Local Government. ABSTRAK Penelitian ini dilakukan di sepuluh kota dan kabupaten di Provinsi Jawa Barat. Penelitian ini bertujuan mengetahui sikap Pemerintah Daerah dalam pelaksanaan, hambatan dan solusinya tentang sosialisasi UU ITE. Metode penelitian ini bersifat deskriptif melalui pendekatan kualitatif, teknik Pengumpulan data dilakukan melalui observasi, wawancara mendalam kepada informan kunci, yaitu para Pejabat Daerah atau yang mewakili yang mengetahui tentang sosialisasi UU ITE. Hasil penelitian menunjukkan bahwa sikap Pemerintah Daerah Jawa Barat terhadap pelaksanaan Sosialisasi, bila dilihat dari aspek pemahaman, aspek ketertarikan dan kesadaran terhadap pentingnya pelaksanaan sosialisasi, menyatakan paham, tertarik dan sadar betul bahwa sosialisasi UU ITE sangat penting.Sejauh ini hanya dua daerah yang telah melaksanakan sosialisasi. Solusinya dengan mengirim perwakilan dari Daerah untuk ikut sosialisasi di Pusat atau Propinsi dan menyiapkan materi dan dana khusus untuk sosiali UU ITE. Kata Kunci: Sosialisasi, UU ITE, Pemerintah Daerah